2019
DOI: 10.3390/joitmc5040083
|View full text |Cite
|
Sign up to set email alerts
|

The Study on the Difference in Corporate Performance and Employment Outcomes According to the Results of Equity-Based Crowdfunding Investment

Abstract: The purpose of this study is to identify the difference in firm performance and employment growth between successful and failed capital procurement through equity-based crowdfunding. We conduct an empirical analysis using entire crowdfunding projects that attempted to raise capital through equity-based crowdfunding in South Korea in 2016. We summarize our findings as follows. Descriptive statistics show that the survival rate, sales growth rate, profitability growth, absolute employment growth, and employment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…The studies of the impact of technology startups on employment mostly have focused on the role of job creation [6,8,12]. One study showed that job creation turned out to be higher in knowledge services sectors than manufacturing industries [13].…”
Section: Technology Startups and Employment Changementioning
confidence: 99%
“…The studies of the impact of technology startups on employment mostly have focused on the role of job creation [6,8,12]. One study showed that job creation turned out to be higher in knowledge services sectors than manufacturing industries [13].…”
Section: Technology Startups and Employment Changementioning
confidence: 99%
“…In innovation, constructs like level of innovation (Gartner et al , 1999; Fritsch and Schindele, 2011; Tsvetkova et al , 2014; Hyytinen et al , 2015) and form of innovation such as product, process and organisational innovation (Xi et al , 2020) were discussed in eight studies. In employment, constructs like the level of employment (Huynh et al , 2012; Baptista et al , 2014; Lerner et al , 2018), employment density (Saboe and Condliffe, 2020) and employment outcomes such as absolute employment growth and employment growth rate (Wagner, 1994; Fritsch et al , 2006; Fritsch and Schindele, 2011; Cho et al , 2019) were discussed in seven studies. The impact of the sector of activity of the firm (Navarro, 2018; Caliendo et al , 2020; Del Sarto et al , 2020) was examined in six studies.…”
Section: Synthesis and Findingsmentioning
confidence: 99%
“…Some studies (2018) find that equitycrowdfunded firms have a higher failure rate than non-equity-crowdfunded firms, which can be caused by adverse selection problems (Walthoff-Borm, Vanacker, and Collewaert, 2018). Other studies find that survival rate, sales growth, employment growth and revenues are higher for start-ups with a successful crowdfunding campaign than for companies with failed crowdfunding (Cho, Park, and Sung, 2019).…”
Section: Financing Forms Of Start-ups In Relation To Start-up Perform...mentioning
confidence: 99%